The Human Cytomegalovirus Chemokine vCXCL-1 Modulates Normal Dissemination Kinetics of Murine Cytomegalovirus In Vivo - Joseph W. Jackson (American Society for Microbiology, 2019)
ABSTRACT Human cytomegalovirus (HCMV) is a betaherpesvirus that is a significant pathogen within newborn and immunocompromised populations. Morbidity associated with HCMV infection is the consequence of viral dissemination. HCMV has evolved to manipulate the host immune system to enhance viral dissemination and ensure long-term survival within the host. The immunomodulatory protein vCXCL-1, a viral chemokine functioning primarily through the CXCR2 chemokine receptor, is hypothesized to attract CXCR2+ neutrophils to infection sites, aiding viral dissemination. Neutrophils harbor HCMV in vivo; however, the interaction between vCXCL-1 and the neutrophil has not been evaluated in vivo. Using the mouse model and mouse cytomegalovirus (MCMV) infection, we show that murine neutrophils harbor and transfer infectious MCMV and that virus replication initiates within this cell type. Utilizing recombinant MCMVs expressing vCXCL-1 from the HCMV strain (Toledo), we demonstrated that vCXCL-1 significantly enhances MCMV dissemination kinetics. Through cellular depletion experiments, we observe that neutrophils impact dissemination but that overall dissemination is largely neutrophil independent. This work adds neutrophils to the list of innate cells (i.e., dendritic and macrophages/monocytes) that contribute to MCMV dissemination but refutes the hypothesis that neutrophils are the primary cell responding to vCXCL-1. IMPORTANCE An adequate in vivo analysis of HCMV’s viral chemokine vCXCL-1 has been lacking. Here we generate recombinant MCMVs expressing vCXCL-1 to study vCXCL-1 function in vivo using MCMV as a surrogate. We demonstrate that vCXCL-1 increases MCMV dissemination kinetics for both primary and secondary dissemination. Additionally, we provide evidence, that the murine neutrophil is largely a bystander in the mouse’s response to vCXCL-1. We confirm the hypothesis that vCXCL-1 is a HCMV virulence factor. Infection of severely immunocompromised mice with MCMVs expressing vCXCL-1 was lethal in more than 50% of infected animals, while all animals infected with parental virus survived during a 12-day period. This work provides needed insights into vCXCL-1 function in vivo.